Characterizations of the Shunkov groups - Senashov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
The structure of the family of finite subgroups of the form Lg = ‹a, ag › in periodic Shunkov’s group is studied. As a colorraries of the result obtained, two characterizations of periodic Shunkov’s groups follow.